2003
DOI: 10.1016/s1388-9842(03)00148-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of peroxisome proliferator‐activated receptor gamma (PPARγ) expression in arteries and hearts of patients with ischaemic or dilated cardiomyopathy

Abstract: PPARg, a nuclear transcription factor, is expressed in various cells within the vasculature and in cardiomyocytes. It has been suggested that PPARg is involved in atherogenesis and in cardiac hypertrophy. Therefore, we sought to quantify PPARg mRNA in coronary arteries, the aorta and left ventricular specimens from patients with ischaemic (CHD) and dilated cardiomyopathy (CMP). Using real-time PCR, we were able to demonstrate the expression of PPARg in all of the human specimens. The lowest expression of PPARg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Wang et al [19] indicated that Pparγ plays a significant role in atherogenesis and possibly direct local vascular wall effect. Mehrabi et al [20] found increased Pparγ mRNA level in patients with ischaemic and dilated cardiomyopathy, suggesting an important function in the pathogenesis of heart diseases. Our finding that the heart gene expression levels of all genes analysed were generally increased in diabetic subjects suggests metabolic dependency.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [19] indicated that Pparγ plays a significant role in atherogenesis and possibly direct local vascular wall effect. Mehrabi et al [20] found increased Pparγ mRNA level in patients with ischaemic and dilated cardiomyopathy, suggesting an important function in the pathogenesis of heart diseases. Our finding that the heart gene expression levels of all genes analysed were generally increased in diabetic subjects suggests metabolic dependency.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, PPARγ is expressed at relatively low levels in the heart [11][14] and recent data have shown that tissue specific loss of PPARγ have no effect on expression of gene controlling lipid and glucose metabolism [15]. Furthermore, exposure of myocytes to PPARα or α/γ specific agonists or long-chain fatty acids led to a significant induction of known PPAR target genes involved in fatty acid uptake and oxidation whereas a PPAR agonist had no effect [12].…”
Section: Introductionmentioning
confidence: 99%
“…In rodents, TZDs have been shown to cause cardiac hypertrophy during chronic treatment [38]. Interestingly, left ventricular specimens from patients with dilated cardiomyopathy exhibit a significant increase in PPAR-γ expression, whereas the expression of PPAR-γ is nearly undetectable in the healthy heart [39]. These observations have led to speculation that PPAR-γ may be involved in cardiac hypertrophic growth programs or in ventricular remodeling.…”
Section: Role Of Ppar-γmentioning
confidence: 99%